Robbench: Can Ai Judges Revolutionize Sri Lanka’s Quest for Justice? - Kularathne, P.S.C. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Investigates the potential role of AI in transforming SL’s judiciary system currently burdened with over 1.1 million unresolved cases caused by outdated paper-based procedures, limited digitization, and judicial understaffing. These systemic inefficiencies have eroded public confidence and highlighted the urgent need for reform. Drawing lessons from countries such as China, Estonia, and Brazil where AI has been piloted in judicial settings this study evaluates whether SL can ethically and effectively adopt AI while preserving the integrity of its legal traditions. Adopting a mixed-method, the study integrates qualitative insights from semi-structured interviews with quantitative perspectives. Data was gathered from 106 participants all over the country, comprising 20 lawyers, 40 law students, 15 research officers, 30 members of the public, and an industry expert, Mr. Parakrama Rathnayake of RedBlocks/AI Pazz. This inclusive approach ensured a balanced evaluation across professional, educational, and societal viewpoints. Findings show that AI holds considerable promise for streamlining judicial processes, reducing case backlogs, and enhancing access to justice. However, consensus among stakeholders underscores that AI should function as a supportive mechanism rather than a decision-making authority, thereby safeguarding judicial independence and public trust. Further proposed a phased strategy to integrate AI into judiciary system (1) digitization of judicial processes, (2) introduction of supportive AI tools, (3) pilot projects in low-risk areas, and (4) establishment of ethical and legal safeguards, including a Judicial AI Oversight Commission. Parallel emphasis is placed on capacity-building initiatives training judges, lawyers, and research-officers in AI literacy while fostering public education to mitigate the risks of over-reliance on algorithms.The study concludes that AI can significantly modernize SL’s judiciary and restore confidence in the justice system if introduced gradually, under human control, and aligned with both domestic legal traditions and international ethical standards. AI, therefore, should be viewed not as a replacement for judges, but as a catalyst for creating a more efficient, transparent, and accessible judicial system.
Keywords: Artificial intelligence (AI); Judicial reform; Sri Lanka; Access to justice; Legal ethics